2016
DOI: 10.24841/fa.v25i1.382
|View full text |Cite
|
Sign up to set email alerts
|

Estimación Del Carbono Almacenado en Tres Sistemas Agroforestales Durante El Primer Año De Instalación en El Departamento De Huánuco

Abstract: RESUMENLos sistemas agroforestales (SAF) combinan de manera simultánea o secuencial los árboles maderables y las plantas de cultivos alimenticios, ofreciendo soluciones para los problemas productivos y el uso sostenible de la tierra en las zonas rurales. El objetivo del estudio fue cuantificar la cantidad de carbono en el suelo y la biomasa aérea de tres sistemas agroforestales durante el primer año de instalación. En los SAF se usaron combinaciones de una especie forestal maderable (Guazuma crinita) con tres … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 4 publications
0
3
0
1
Order By: Relevance
“…Some studies conducted in the Peruvian Amazon have analyzed the C distribution in different compartments, in agroforestry systems shaded by one predominant species (Ehrenbergerová et al ., 2016; Timoteo et al ., 2016). Moreover, just a few studies have so far reported the use and diversity of shade trees and their contribution at the species level to the aboveground C stock in polyculture-shaded agroforestry systems in this region (Vebrova et al ., 2014; Pizarro et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies conducted in the Peruvian Amazon have analyzed the C distribution in different compartments, in agroforestry systems shaded by one predominant species (Ehrenbergerová et al ., 2016; Timoteo et al ., 2016). Moreover, just a few studies have so far reported the use and diversity of shade trees and their contribution at the species level to the aboveground C stock in polyculture-shaded agroforestry systems in this region (Vebrova et al ., 2014; Pizarro et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The most common species used in agroforestry are Inga edulis, Guazuna crinite, Calycophyllum spruceanum, C. spruceanum, Cedrela odorata, Mariosousa willardiana, Cajanus cajan, Schizolobium amazonicum, and Leucaena leucocephala. Aboveground carbon stock ranges from 2.9-4.4 Mg/ha in 1-yearold agroforestry systems to 27-32.4 Mg/ha in 20-year-old agroforestry systems, whereas total carbon content ranges from 33.4-37.2 to 168.9 Mg/ha in 1-year-old and 10-year-old agroforestry systems, respectively , Villogas https://www.ecologyandsociety.org/vol27/iss3/art12/ , Timoteo et al 2016). However, the amount of carbon stock in agroforestry systems depends on the tree species, so these values may vary (Appendix 1).…”
Section: Agroforestry Systemsmentioning
confidence: 99%
“…In general, forestry plantations in Peru are small in comparison to the areas dedicated to agriculture and of the 117,495.59 ha of plantations in 2022 the areas dedicated to Guazuma crinita amounted to 15,109.46 ha, representing nearly 12.86% of forestry plantations in the country, and it is also the most planted species in Peru 6 . Even with its high importance, research on this species has focused mostly on genetics 7 9 , developing allometric models 10 , 11 , carbon storage 12 , propagation 13 , wood characteristics 14 or management 15 , 16 , with little known about soil fertility, nutrition requirements or fertilization management in this species, which represent very important issues for future commercial plantations.…”
Section: Introductionmentioning
confidence: 99%